2021
DOI: 10.3390/cancers13051095
|View full text |Cite
|
Sign up to set email alerts
|

From Liver Fat to Cancer: Perils of the Western Diet

Abstract: Hepatocellular carcinoma (HCC), the most common type of primary liver cancer provides the prototypical example of an obesity-related cancer. The obesity epidemic gave rise to an enormous increase in the incidence of non-alcoholic fatty liver disease (NAFLD), a condition that affects one third of American adults. In about 20% of these individuals, simple liver steatosis (hepatosteatosis) progresses to non-alcoholic steatohepatitis (NASH) characterized by chronic liver injury, inflammation, and fibrosis. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 154 publications
0
25
0
Order By: Relevance
“…Other studies on AAV gene delivery to the liver have not detected NASH or HCC. This is expected because all murine models of NASH and HCC progression require a hypercaloric diet, presumably to induce an inflammatory environment (56, 57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on AAV gene delivery to the liver have not detected NASH or HCC. This is expected because all murine models of NASH and HCC progression require a hypercaloric diet, presumably to induce an inflammatory environment (56, 57).…”
Section: Discussionmentioning
confidence: 99%
“…However, our new results show that high levels of FVIII gene expression by itself, even if transient and very likely independent of insertional events, can induce HCC in the context of a HFD. All murine models of NASH and HCC progression require a hypercaloric diet, presumably to induce an inflammatory environment (66, 67). HCC has not been observed in animals treated with AAV-FVIII vectors but these animals were not subjected a HFD challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Among these conditions, simple steatosis of hepatocytes only rarely leads to clinical symptoms; it is also difficult to make a diagnosis, as the only effective method of determination so far is biopsy, which is invasive and thus generally not acceptable to patients who are suspected of having such a disease. However, fatty liver may be a precursor to all of the other, more severe states of liver disease, even cancer ( 54 , 55 ). Understanding the mechanisms underlying the etiology and pathology of fatty liver diseases therefore has definite clinical significance in prevention, early prognosis, and treatment.…”
Section: Fatty Liver and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Thirdly, endotoxemia resulted from increased gut permeability is also associated with NAFLD pathogenesis, indicating the effects of gut dysbiosis on immune system ( 55 ). Bacteria-derived endotoxins such as lipopolysaccharide (LPS) are closely related with intestinal immune function ( 73 ).…”
Section: Gut Microbial Dysbiosis and Nafld: The Gut-liver Axismentioning
confidence: 99%
“…[38] It has been demonstrated that multiple parallel hits drive not only CLD pathogenesis, but also the development of HCC on the background of CLD. [39] Although environmental exposure is increasingly identified as a potential risk factor for CLD, [40] few studies have investigated the impact of environmental exposure on the risk of developing HCC. The purpose of this study is to begin to address this gap in our knowledge.…”
Section: The Enhancement Of Hcc By Vc Exposure Leads To a Unique Epit...mentioning
confidence: 99%